House dust mites confer a distinct immunological feature among dermatitis - (:unkn) unknown (Iranian Journal of Allergy, Asthma and Immunology, 2016)
Atopic dermatitis (AD) is a heterogeneous disease with regard to clinical phenotype and natural history. We investigated T cell subtypes and cytokine responses in peripheral blood and skin lesions of AD patients with various sensitivities. Immunological studies were performed in 27 subjects: 9 house dust mite (HDM)-sensitized; 6 subjects with sensitizations other than HDM; 7 non- Allergic AD patients and 5 healthy controls. Among those, skin biopsy samples of 13 subjects were evaluated for immunohistochemical analyses, as well. The mean age was 8.93±5.17 years. HDM- Allergic AD emerged as a distinct immunologic phenotype, with higher production of interleukin (IL)-4, -5, -2 both at rest and when stimulated by Der p1 or SEB along with higher Th17. As for TH17 cell percentage, it was increased in all AD groups compared to healthy controls, while HDM- Allergic group was distinguished with a significantly lower production of IL-17. Patients with sensitizations other than HDM were mostly similar to non- Allergic AD, with increased Th17 and CD4+CD69+interferon-gamma (IFN-γ)+ T cells percentage. The biopsy of lesional skin showed that HDM- Allergic AD had lower IFN-γ and IFN-γ co-expressing CD8+ T cells compared to patients with other sensitizations (p=0.03 and p=0.04, respectively). Among the HDM allergic patients, pairwise comparison of lesional versus non-lesional skin revealed higher CD4+ T cells numbers, expression of forkhead box P3 (Foxp3) and T-cell-specific transcription factor (T-bet) (p=0.018, p=0.018, p=0.018, respectively). HDM- Allergic AD is a distinct subtype with a predominant skewing in Th2 and higher Th17 cell percentage along with a blunted Th1 response in the skin, all of which may have therapeutic implications. © Summer 2016, Iran J Allergy Asthma Immunol. All rights reserved.
Keywords: Atopic dermatitis; House dust mite; Interferon-gamma; Skin lesion; Th17 cells